ChemInform Abstract: Catalytic Paradigms: A Riddle and a Puzzle. Issue 46 (18th November 2014) - van Santen, Rutger A.
Abstract Review: aspects of computational chemistry as well as kinetics and physical state of the reactive catalyst, 22 refs.